Role of dietary therapy in managing epilepsy in children - Babonji, Mohammed Saeed; Alkhatir, Zahra Abdullah; Alharbi, Adel Abed; Alghasham, Buthaynah Abdullah; Abumansour, Ola Lateef; Ali, Majed Hassan; Ali, Walaa Mohamed; Alrajhi, Nermeen Nasser; Al Mohammed, Abdulaziz Ali; Alhasani, Mutasim Hassan; Algethami, Saad Shaker; Alzanbagi, Salah Mohammed (International Journal Of Community Medicine And Public Health, 2021)
Ketogenic diets have been proposed as effective management approaches that have been validated by many studies in the literature. The efficacy of administering these treatment modalities has been validated by many studies within epilepsy-related syndromes as Rett syndrome, infantile spasms, GLUT-1 deficiency and Dravet syndrome. As a result, it has been noticed that observable favorable outcomes within the first three months from starting the administration of these treatment regimens. In this literature review, we have discussed the dietary therapeutic approaches for managing epilepsy in children. The findings have been combined from different studies in the literature. Many of them are comparative investigations that have indicated the efficacy of these treatment plans in reducing both the frequency of seizures and adequately inhibiting the development of further epilepsy events. Many mechanisms have been proposed for these treatment modalities to inhibit seizures that are adequately discussed in this article. Based on the current evidence, further awareness approaches should be conducted to increase the administration of these products, especially in pharmaco-resistant cases.